Isolation and characterization of a novel highly efficient bacterium Lysinibacillus boronitolerans QD4 for quantum dot biosynthesis - Gu, Xingyu; Li, Xiaoju; Zhang, Ruijia; Zheng, Ruoli; Li, Mingrui; Huang, Rong; Pang, Xin (Frontiers in Microbiology, 2025)
Microorganism-based biosynthesis of quantum dots is a low-cost and green production method with a wide range of potential applications. The development of environmentally friendly synthesis methods is required due to the toxicity and severe reactions that occur during the chemical synthesis of quantum dots. In this study, a novel strain, QD4, with the ability to the effectively and rapidly biosynthesize CdS quantum dots, is isolated and reported. The isolated strain is a Gram-positive, aerobic, flagellated, and rod-shaped bacterium, isolated from seawater. Through the physio-biochemical characterization and 16S rRNA-based phylogenetic tree analysis, the strain is identified as Lysinibacillus boronitolerans QD4. The strain QD4 grows well in the range of 25–40 °C (optimum, 37 °C), pH 5.0–9.0 (optimum, pH 7.0), with a high cadmium-resistance as it could grow at Cd2+ concentration up to 2 mM, implying its good adaptability to the environment and potential for application. Cd2+ and L-cysteine are used as substrates for the biosynthesis of CdS quantum dots by strain QD4. The distinctive yellow fluorescence from CdS quantum dots is visible after only a short induction time (a few hours). Moreover, the properties of the CdS quantum dots are characterized by fluorescence spectroscopy, UV-absorption spectroscopy, TEM, XRD, XPS, and infrared spectroscopy. This study provides a novel strain resource for efficient biosynthesis of extracellular, water-soluble quantum dots, paving potential industrial applications in green production.